Prospective observational study of cervical cancer screening by Pap smear in tertiary care hospital in hilly areas of Himachal Pradesh - Justa, Usha; Mittal, Rita; Negi, Kalpna; Rathore, Sandeep; Sharma, Surabhi; Choudhary, Asha; Rawat, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer is major cause of morbidity and mortality in females. The majority of cervical cancer deaths are in developing, low- and middle-income countries. India is having highest age standardization incidence of cancer cervix at 22. Cancer cervix is major health problem and rank one malignancy in Himachal Pradesh. This study was an attempt to detect various lesions of cervix with the help of Pap smear as a screening tool and timely intervention of any abnormality. Methods: Total 2139 women in age group of 21-65 years were screened by Pap smears who presented in OPD for various gynaecological complaints and as a routine beyond 45 years. The study was conducted at Kamla Nehru State Hospital Shimla Himachal Pradesh during period of 01.02. 2023 to 31.07. 2023. Pap smear testing was done by conventional method and reported according to Bethesda system. Results: In the present study majority of women were in age group of 41-50 years (49.56%). On analysis of Pap smears 86.11% samples were reported as negative for intraepithelial lesion or malignancy (NILM). Atypical squamous cells of undetermined significance were found in 1.12%, low grade intraepithelial lesion 0.23%, high grade intraepithelial lesion 0.19%, adenocarcinoma and squamous cell carcinoma 0.05% each. On further sub categorization of NILM cytology reports inflammatory finding was commonest (52.06%). Conclusions: Early and routine Pap smear screening is important for early diagnosis of premalignant cervical lesions and Cancer cervix as prevention is better than cure.